Efficacy of gamma irradiated Steinernema carpocapsae BA2 against ( 47 ) Journal of Corcyra cephalonica and Ephestia kuehniella (Journal of Nuclear Technology in Applied Science, 2023)
The effect of different doses of gamma radiation (2, 4, 6, 8, and 10 Gy) on the infective juveniles (IJs) of Steinernema carpocapsae was studied. The results showed a positive correlation between mortality and the storage period of the infective juveniles. The susceptibility of Corcyra cephalonica and Ephestia kuehniella to both unirradiated and gamma-irradiated (2 and 3 Gy) Steinernema carpocapsae was evaluated based on daily larval mortality. It was observed that larval mortality increased when gamma-irradiated nematodes were used, as they required less time to cause larval morbidity. In contrast, the reproductive rate of the nematodes decreased after irradiation.
Keywords: Entomopathogenic Nematodes; Control; Gamma Radiation; Moth; Broccoli Heads Powder; Broccoli Leaves Powder; Low Caloric Cake; Replacement; Total Phenolic Compounds; Antioxidant; Physical Properties; Sensory Properties